2014
DOI: 10.1002/asna.201412062
|View full text |Cite
|
Sign up to set email alerts
|

Jets from young stars and brown dwarfs

Abstract: The protostellar outflow mechanism operates for a significant fraction of the pre-main sequence phase of a solar mass star and is thought to have a key role in star and perhaps even planet formation. This energetic mechanism manifests itself in several different forms and on many scales. Thus outflow activity can be probed in numerous different regimes from radio to X-ray wavelengths. Recent discoveries have shown that it is not only solar mass stars that launch outflows during their formation but also the sub… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…The peak velocity of the H 2 and [Fe II] emission is measured at (-35 ± 2) km s −1 and (-51 ± 5) km s −1 respectively. These radial velocities are in line with the radial velocities of Class II BD outflows (Whelan, 2014a). A 2D fitting of the emission Velocities have been corrected for the systemic velocity of the source.…”
Section: Outflow Morphology Kinematics and Physical Propertiessupporting
confidence: 58%
See 1 more Smart Citation
“…The peak velocity of the H 2 and [Fe II] emission is measured at (-35 ± 2) km s −1 and (-51 ± 5) km s −1 respectively. These radial velocities are in line with the radial velocities of Class II BD outflows (Whelan, 2014a). A 2D fitting of the emission Velocities have been corrected for the systemic velocity of the source.…”
Section: Outflow Morphology Kinematics and Physical Propertiessupporting
confidence: 58%
“…The first studies ofṀ out /Ṁ acc in BDs concentrated on Class II sources and values were found to be > 1 which is inconsistent with models. Improvements in data and methods led to a better constrained estimate for one Class II BD ISO-Cha I 217 (Whelan, 2014a). Observations of proto-BD jets have to date been confined to optical data which has led to problems with estimates of jet efficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…young brown dwarfs (0.08 M to 0.13 M ) (e.g., Whelan et al 2005). Although numerous outflows have been detected in the mass range from brown dwarfs to very low mass stars (0.13 M to 0.2 M ), in a majority of the cases, these are micro-jets with projected lengths of ≤0.03 pc (e.g., Whelan 2014). The brown dwarfs or very low-mass stars driving these micro-jets are all optically visible, and are therefore taken to be analogous to Class II YSOs.…”
Section: While Most Of What Is Understood About Outflows Comes From O...mentioning
confidence: 99%
“…Firstly, this can be done by taking observations using orthogonal slit PAs and combining the offsets measured to estimate a direction and PA for the spatial offsets. This method has been adopted to assign directions and PAs to BD outflows (Whelan 2014;Whelan et al 2012). Secondly, 2D SA can be acheived in a more direct way by analysing integral field spectra (IFS).…”
Section: Spectro-astrometrymentioning
confidence: 99%